2013
DOI: 10.5539/ass.v9n10p307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of IT knowledge and IT Training on the IT Utilization among External Auditors: Evidence from Yemen

Abstract: This study aimed to investigate the level of IT utilization and the factors that influence the IT utilization among the audit practitioners in Yemen. The proposed model investigates the impact of IT knowledge, IT training and firm category on the IT utilization. The researchers use a survey questionnaire, the data were collected from 197 external auditors representing Big-4 and non-Big-4 firms operating in Yemen. The Partial Least Squares (PLS) Structural Equations Modeling Approach was employed to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Previous studies assert that high IT proficiency among auditors would lead to increased GAS use (Brazel et al , 2010, Li et al , 2007). A recent study found the effect of IT knowledge and training increased IT use (Al-Ansi et al , 2013). Table III shows that while participants agreed that good IT skills are essential for increased GAS use, they recognized that IT skill levels varied substantially among staff.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Previous studies assert that high IT proficiency among auditors would lead to increased GAS use (Brazel et al , 2010, Li et al , 2007). A recent study found the effect of IT knowledge and training increased IT use (Al-Ansi et al , 2013). Table III shows that while participants agreed that good IT skills are essential for increased GAS use, they recognized that IT skill levels varied substantially among staff.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…New users are not experienced in the instructions provided and as such, they have a higher tendency to perceive the provision of additional information cues as useful, although it may not leverage such information to enhance their work performance (Cukier et al, 2012). Thus, it can be stated that experience of information technologies fit affects individual performance through the attitude towards information technology use (Al-Ansi et al, 2013).…”
Section: Literature On Information Technologymentioning
confidence: 99%
“…If audit firms are not updated in terms of computerized IS usage, they cannot meet the many challenges and risks posed by a technology-based business environment. Moreover, auditors with limited knowledge of IT, IT training, and IT use will lack the ability to audit typical customers with complex computer systems (Al-Ansi et al, 2013). This research highlights the types of risk associated with the use of computerized AIS faced by external auditors in enterprises under auditing.…”
Section: Introductionmentioning
confidence: 96%